Narrative Texts: An Error Analysis Of Students In Past Tense Usage - Maskhurin Fajarina; Yuyun Bahtiar (Peneliti.net, 2022)
The purpose of this research is to analyze student errors in the use of past tense in Narrative text paragraphs based on the problems studied students feel confused with the use of the past tense in the narrative text. This thesis is a qualitative descriptive method. The object of research is grade X-A in the 2021/2022 academic year at Islamic Senior High School Darul Ulum Widang -Tuban. From the findings in the field, the researchers found that there are four types of errors, namely: omission, addition, misformation, and misordering. Then, the researchers studied and concluded that the highest number of errors was misformation with the result of 52%. This is because students feel confused about translating words from English Indonesian to English verse. Students can't tell the difference either between regular or irregular verbs. Students also admitted that they rarely practice for make paragraphs in English